Behold the man : Jesus and Greco-Roman masculinity - Conway, Colleen M. (Oxford ; New York : Oxford University Press, 2008)
In this book, Colleen Conway looks at the construction of masculinity in New Testament depictions of Jesus. She argues that the New Testament writers necessarily engaged the predominant gender ideology of the Roman Empire, whether consciously or unconsciously. Although the notion of what constituted ideal masculinity in Greek and Roman cultures certainly pre-dated the Roman Empire, the emergence of the Principate concentrated this gender ideology on the figure of the emperor. Indeed, critical to the success of the empire was the portrayal of the emperor as the ideal man and the Roman citizen a.
Introduction: Jesus and gender -- How to be a man in the Greco-Roman world -- Constructing the lives of divine men : Divus Augustus, Philo's Moses, and Philostratus's Apollonius -- The unmanned Christ and the manly Christian in the Pauline tradition -- The Markan Jesus as manly martyr? -- The Matthean Jesus : mainstream and marginal masculinities -- The Lukan Jesus and the imperial elite -- "He must increase" : the divine masculinity of the Johannine Jesus -- Ruling the nations with a rod of iron : masculinity and violence in the book of Revelation -- Conclusion: The multiple masculinities of Jesus.
Includes bibliographical references (pages 223-242) and indexes.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Criticism, interpretation, etc; Jesus Christ -- Person and offices; Jezus, -- van Nazareth, -- 4 v.Chr.-29 n.Chr.; Men in the Bible; Masculinity -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Men (Christian theology); RELIGION -- Biblical Studies -- New Testament; Sekseverschillen; Mannelijkheid; Griekse oudheid; Romeinse oudheid; Electronic books